The Relevance Of Different Aspects Of Sustainability For The Albanian Tourism Hotels - Gaspari, Alda; Cela, Miresi (European Scientific Journal, ESJ, 2016)
This study is focused on albanian tourism hotels and their orientation towards sustainability. Personal interests of accommodation units owners have made the current development of tourism chaotic and unsustainable. A hotel sustainability business model that was introduced first in Slovenia will be used to investigate the relevance that albanian tourism hotels put to the sustainability dimensions. The aim is to highlight which of three aspects is neglected and takes less attention than others. How important are the different aspects of sustainability (indicators) for albanian hotel owners and managers? Did they measure and monitor these indicators. The main findings stresses that they do not pay the same attention and importance to all aspects of sustainability.